Hubungan Antara Fungsi Keluarga dengan Kejadian Infeksi Saluran Pernapasan Akut (ISPA) pada Anak Balita di Puskesmas Kartasura - Haptianingsih, Baiq Yunita; , Dr. Yusuf Alam Romadhon, M.Kes (2017)
Respiratory tract infections (RTIs) is widely known as one of the major terminal diseases especially those of baby and under-5 children in developing country. RTI is the major reason of morbidity and mortality on infectious disease around the world. In Indonesia, there is still families wherein health is not well maintained; thereby, nutrition is not sufficient; growth and development is distracted; a high number of mortality and morbidity on under-5 children. The aim of this research is to analyze the relationship between function of family and occurrence of RTI on under-5 children, study case of Puskesmas Kartasura. Observational analytics method is employed to analyze; using data of cross-sectional and cluster random sampling as data collection. Up to 80 mothers of under-5 children were chosen to be the sample of research. A questionnaire of 47 preference declarations and 2 questions were given. Univariate analysis and bivariate analysis are employed using Chi-Square.The result revealed that over 80 respondents with healthy family function, 36 mothers (45.0%) have healthy children, while 17 mothers (21.3%) have children with RTI; in unhealthy family function, 8 mothers (10.0%) have healthy children, while 19 mothers (23.8%) have children with RTI. The value of p-value is < 0,01 (0.001)-meaning the result is significant.To conclude, it is revealed that function of family is significantly correlated with occurrence of RTI on under-5 children.